2018
DOI: 10.7577/njcie.2757
|View full text |Cite
|
Sign up to set email alerts
|

Principle of Singularity

Abstract: This paper provides insight into the legislative process behind the current Education Act of Sweden. The aim is to shed light on how and why it came to prohibit joint leadership for principals. Joint leadership is a sub-form of shared leadership between managers characterised by complete formal authority, hierarchic equality and merged work tasks. The sharing of a principal’s position is, in previous research, identified as potentially favourable for principals and schools as it decreases principals’ often hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…FSL as a solution challenges the Swedish Education Act (2010:800), which is essentially based on a belief in the solo qualified leader, and on that basis identifies the principal/pre-school manager as responsible for a wide range of tasks (Döös et al, 2018a;Örnberg, 2016). It remains an open question whether or to what extent the present change would have been easier had the Education Act not restricted the use of the titles principal and pre-school manager.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FSL as a solution challenges the Swedish Education Act (2010:800), which is essentially based on a belief in the solo qualified leader, and on that basis identifies the principal/pre-school manager as responsible for a wide range of tasks (Döös et al, 2018a;Örnberg, 2016). It remains an open question whether or to what extent the present change would have been easier had the Education Act not restricted the use of the titles principal and pre-school manager.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that using West's (1978) terminology (principal of instruction and principal of administration) would have made a favorable difference in addressing the status problem identified. Court (1998), Eckman (2007) and Döös et al (2018a) have all identified problems concerning legal obstacles and questioning from outside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation